Heritability of the extra-pair mating behaviour of the pied flycatcher in Western Siberia - Grinkov, Vladimir G.; Bauer, Andreas; Sternberg, Helmut; Wink, Michael (PeerJ, 2020)
Males and females take part in extra-pair copulations in most socially monogamous bird species. The mechanisms leading to the frequent occurrence of extra-pair offspring in socially monogamous couples are strongly debated and unresolved, and they are often difficult to distinguish from one another. Most hypotheses explaining the evolution of extra-pair reproduction suggest selective and adaptive scenarios for their origination and persistence. Is extra-pair paternity a heritable trait? We evaluated the heritability of extra-pair paternity in the pied flycatcher (Ficedula hypoleuca) nesting in Western Siberia. Estimated heritability was low: depending on the model used, the point estimate of the heritability (mode) varied from 0.005 to 0.11, and the bounds of the 95% confidence interval are [0-0.16] in the widest range. Thus, it seems that extra-pair mating behaviour in the pied flycatchers is a plastic phenotypic mating tactic with a small or no genetic component. Our data can help to understand the evolution of extra-pair mating behaviour in socially monogamous species.
Gesehen am 15.10.2020